2019
DOI: 10.1002/jobm.201800581
|View full text |Cite
|
Sign up to set email alerts
|

Factors driving the distribution and role of AOA and AOB in Phragmites communis rhizosphere in riparian zone

Abstract: Ammonia oxidation, mainly driven by ammonia‐oxidizing archaea (AOA) and bacteria (AOB), plays an important role in determining the rate of nitrification in riparian zones. However, the underlying factors driving the distribution and activity of AOA and AOB in riparian zones, especially in the rhizosphere of Phragmites communis remain unknown. This study revealed the dominance of AOA in ammonium oxidization with higher abundance and activity in both rhizosphere and bulk soil in summer and winter over AOB in rip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…In this study, the NH 4 + ‐N concentration of the sediment has a negative correlation with comammox amoA abundance, which was similar to the findings of a study of tidal flat sediments in the Yangtze River estuary (Jiang et al ). Moreover, the NH 4 + ‐N concentration of the sediment has no significant correlation with AOA amoA or AOB amoA gene, which was similar to the study of rhizosphere sediments of riparian zone (Wang et al ). This was likely due to the relatively high NH 4 + ‐N concentration in lake sediments (19·12–44·13 mg kg −1 ) in this study, compared to that in soils (7–20 mg kg −1 ) (Shi et al ).…”
Section: Discussionsupporting
confidence: 83%
“…In this study, the NH 4 + ‐N concentration of the sediment has a negative correlation with comammox amoA abundance, which was similar to the findings of a study of tidal flat sediments in the Yangtze River estuary (Jiang et al ). Moreover, the NH 4 + ‐N concentration of the sediment has no significant correlation with AOA amoA or AOB amoA gene, which was similar to the study of rhizosphere sediments of riparian zone (Wang et al ). This was likely due to the relatively high NH 4 + ‐N concentration in lake sediments (19·12–44·13 mg kg −1 ) in this study, compared to that in soils (7–20 mg kg −1 ) (Shi et al ).…”
Section: Discussionsupporting
confidence: 83%
“…There were also significant and negative correlations between AOA abundance and sediment metals (Table 1), suggesting that higher metal levels in vegetated sediments maybe toxic to AOA (Liu et al 2014). In line with our results, significantly higher AOA and AOB abundances in the bulk soils than in the Phragmites communis rhizosphere soils were also found in the riparian zone (Wang et al 2019).…”
Section: Abundances Of Aob and Aoa In The Seagrass Systemsupporting
confidence: 89%
“…It was interesting that in the N-limited (NH 4 + ≤ 660 μmol g −1 ) Z. marina sands of Tanoura Bay, Nitrosospira dominated in the in situ AOB community, but after the enrichment incubation with 4 mM NH 4 + , the dominant AOB population shift to Nitrosomonas (Ando et al 2009). Furthermore, from the view of habitat selection, Nitrosomonas mainly occurs in marine sediments (Zhang et al 2015b;Ling et al 2018), while Nitrosospira was more adaptable in soils and freshwater sediments (Jia and Conrad 2009;Wang et al 2019) (Table 3).…”
Section: Seagrass Colonization Selected Specific Lineages Of Ammonia Oxidizersmentioning
confidence: 99%
“…The dominant genera of AOB, Nitrosospira , accounted for about 99% of all AOB sequences, which may be due to the low NH 4 + level in the riparian zone (Table 1), where Nitrosospira has a stronger competitive survival ability than Nitrosomonas . These results showed that Nitrosospira may be essential for the ammonia oxidation of bacteria in the riparian zone [48].…”
Section: Discussionmentioning
confidence: 99%